Evaluasi Performa Website Pantipendowokudus.com terhadap Pengalaman Pengguna Disabilitas Netra - Muhammad Sholikhan; Nur Fajrie; Imaniar Purbasari (Lembaga Pengembangan Kinerja Dosen, 2024)
Website accessibility is essential for guaranteeing that digital services are accessible to all users, including those with visual impairments. This research assesses the accessibility of the Panti Pendowo website in accordance with the Web Content Accessibility Guidelines (WCAG) 2.1 standards and utilises the Google Lighthouse evaluation tool. The findings reveal that the page loading speed received a score of 70, website responsiveness 80, code efficiency 65, and heading structure 60. Nonetheless, notable deficiencies were noted, including inadequate colour contrast (50), ineffective keyboard navigation (55), and insufficient utilisation of alternate text for images (40). The findings indicate that although the website functions adequately, enhancements in accessibility are necessary. Essential recommendations encompass improving colour contrast, optimising keyboard navigation, clarifying heading hierarchies, and incorporating alternate text for images. The enhancements intend to render the website more inclusive and to enhance the user experience for visually impaired persons.